BUDAYA ETIS ORGANISASI SEBAGAI VARIABEL PEMODERASI PENGARUH ORIENTASI ETIS PADA PERTIMBANGAN ETIS AUDITOR - Putra, Ni Ketut Apriliawati; Suardana, Ketut Alit (E-Jurnal Akuntansi; Vol 17 No 2 (2016), 2016)
This study was conducted to determine the ethical culture of the organization as the moderating variable influence ethical orientation on ethical considerations auditor. This research was conducted in Bali, samples taken as many as 80 people with purposive sampling method. The data collection is done by distributing questionnaires using Likert scale of 4 points to measure 28 indicators. The analysis technique used is moderated regression analysis. These results indicate that the orientation of ethical idealism positive influence on ethical considerations auditor, the orientation of ethical relativism negative effect on ethical considerations auditor, ethical culture organization moderating influence ethical orientation idealism on ethical considerations auditor, ethical culture organization moderating influence of the orientation of ethical relativism on the ethical considerations auditor , This shows that the ethical organizational culture variables able to moderate the influence of ethical orientation on ethical considerations auditor.
Keywords: Organizational Ethical Culture, Orientation Ethical, Ethical Considerations Auditor